Kết quả ứng dụng phương pháp xử lý khe nứt nội lớp trầm tích để nghiên cứu trạng thái cổ ứng suất và quy luật địa động lực của vỏ Trái Đất vùng Tây Bắc Việt Nam - Lư, Ngô Thị; Belousov, T.P.; Kurtasov, S.F.; Thắng, Ngô Gia; Quang, Nguyễn; Tùng, Nguyễn Thanh; Dũng, Lê Văn; Tuyên, Nguyễn Hữu; Hoãn, Vũ Thị; Phương, Trần Việt; Hằng, Phùng Thị Thu (Vietnam Journal of Earth Sciences, 2012)
SUMMARYThe applying results of inner-layer fracture analysis to study geodynamic regularities and paleo-stress conditions and geodynamics of the Earth’s crust of Northwest VietnamThis paper presents results of fracture investigations in Northwest Vietnam using new inner-layer fracture analysis method and computer processing data. The fractures of sediments of different ages (from Precambrian to Quaternary) are messured and analysed. The studied results are presented by the stereograms for orientating distribution of the fractures and roses-diagrams for azimuthal direction of fracture's systems. Based on these results, we can de termine structural characteristics of the fracture systems and geodynamic regimes as wellas the Earth's crust evolution of Northwest Vietnam.